Assessment of the Determinants of Auditors’ Effectiveness in the Detection and Prevention of Corporate Fraud in Nigerian Commercial Banks - Lawal, Sakiru Abiola (European Journal of Life Safety and Stability (2660-9630), 2022)
The specific aim of this study was to find out the determinants of auditors’ effectiveness in the detection and prevention of corporate fraud in Nigerian Commercial Banks with Eco bank as a case study. Descriptive survey research design was adopted for the study. The study was conducted in Lagos. The population of the study comprised of all the auditors; management and other senior staff of Eco bank in Nigeria. Simple random sampling technique was used to select 155 respondents that constituted the sample size used for the study. The instrument titled “DETERMINANTS OF AUDITORS’ EFFECTIVENESS IN THE FRAUDS DETECTION AND PREVENTION QUESTIONNAIRE (DAEFDPQ)” was used for data collection. In order to ensure validity and reliability of research instrument, a pre-test was conducted using the test- retest model of reliability and validity. Cronbach Alpha technique was used to determine the level of the reliability of the instrument. In this case the reliability coefficient obtained was 0.91 and this was high enough to justify the use of the instrument. The researcher subjected the data generated for this study to appropriate statistical analysis such as descriptive statistics used in answering research questions and simple regression used in testing the hypotheses. The test for significance was done at 0.05 alpha levels. Auditors are required to be more proactive in searching for fraud during the course of an audit. Auditors are also expected to inquire more closely into reasons behind such matters as, for example, errors in accounting estimates, unusual transactions that appear to lack business rationale, and a reluctance to correct immaterial errors discovered by the audit. Apparently, the study concluded that there is no significant effect of auditor’s experience on the detection and prevention of fraud in Eco bank. Secondly, there is significant effect of auditors’ training on the detection and prevention of fraud in Eco bank. Then finally, auditor’s quality significantly affects the detection and prevention of fraud in Eco bank. One of the recommendations made amongst others is that auditors should always ensure that they acquire necessary professional qualifications as well as training professionally and technically for quality job performance.